Surface influence on the rotational and translational dynamics of molecules confined inside a mesoporous carbon xerogel. (17th January 2019) - Cadar, Calin; Ardelean, Ioan
Abstract: Low‐field nuclear magnetic resonance techniques are employed to extract information about the effects introduced by the interaction with the surface on the rotational and translational dynamics of molecules confined inside a mesoporous carbon xerogel. The molecules under study were water, cyclohexane, and hexane. They were chosen due to their different interaction strength with the carbonaceous matrix. Frequency dependent longitudinal relaxation measurements, using the fast field cycling technique, allowed extraction of the fractal dimension of the carbon xerogel surface. It was observed that the measured value is influenced by the molecule affinity to the surface. Diffusion measurements, using the pulse field gradient technique, have revealed that the stronger interaction with the surface of cyclohexane and hexane molecules leads to an increased diffusive tortuosity, as compared with water. Abstract : The work exploits low‐field nuclear magnetic resonance relaxometry and diffusometry techniques to extract information about the effects introduced by the interaction with the surface on the rotational and translational dynamics of water, cyclohexane, and hexane molecules confined inside a mesoporous carbon xerogel. Relaxation studies allowed extraction of information about liquid distribution inside pores and the fractal dimension of the xerogel surface. Diffusion measurements have demonstrated a direct relationship between the diffusive tortuosity and the interaction strength.